2010
DOI: 10.1073/pnas.1011043107
|View full text |Cite
|
Sign up to set email alerts
|

Short-term meditation induces white matter changes in the anterior cingulate

Abstract: The anterior cingulate cortex (ACC) is part of a network implicated in the development of self-regulation and whose connectivity changes dramatically in development. In previous studies we showed that 3 h of mental training, based on traditional Chinese medicine (integrative body-mind training, IBMT), increases ACC activity and improves self-regulation. However, it is not known whether changes in white matter connectivity can result from small amounts of mental training. We here report that 11 h of IBMT increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
353
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 429 publications
(397 citation statements)
references
References 35 publications
(50 reference statements)
23
353
2
4
Order By: Relevance
“…Sholz et al found that six weeks of juggling training in adults resulted in FA increases in the white matter beneath the right intraparietal sulcus (Scholz et al, 2009). Additional studies now suggest adult FA increases following balance training (Taubert et al, 2010), working memory training in aging participants (Lövdén et al, 2010;Engvig et al, 2011), and meditation training (Tang et al, 2010). A number of reviews and critiques of both the gray matter and white matter changes resulting from relatively long-term, intensive learning or training regimens in adults have recently appeared (Zatorre et al, 2012;Lövdén et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sholz et al found that six weeks of juggling training in adults resulted in FA increases in the white matter beneath the right intraparietal sulcus (Scholz et al, 2009). Additional studies now suggest adult FA increases following balance training (Taubert et al, 2010), working memory training in aging participants (Lövdén et al, 2010;Engvig et al, 2011), and meditation training (Tang et al, 2010). A number of reviews and critiques of both the gray matter and white matter changes resulting from relatively long-term, intensive learning or training regimens in adults have recently appeared (Zatorre et al, 2012;Lövdén et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent mental training and mindfulness research in humans (34-38) has begun to address changes in gray matter volume after the training of higher-level skills, such as present-moment attention and mindfulness based on contemplative practices (38)(39)(40)(41). However, most studies have been cross-sectional, focusing on meditation practitioners and not directly assessing training-related plasticity within training-naïve subjects (42).…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies have been cross-sectional, focusing on meditation practitioners and not directly assessing training-related plasticity within training-naïve subjects (42). The few published longitudinal training studies on structural plasticity to date have mainly assessed the effects of cultivating a rather broad range of mindfulness-related capacities, including attention, acceptance, and interoceptive awareness (39)(40)(41). Notably, samples in these studies were relatively small, and studies often lacked active control groups; furthermore, testing intervals were short, providing neither generalizable and robust estimates of brain change nor information about the effects of different types of mental practices on plasticity (38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…DTI is capable of measuring white matter's structural plasticity. Studies indicate that training or learning alters brain white matter (1)(2)(3)(4)(5). Fractional anisotropy (FA) is an important index for measuring the integrity of white matter fibers.…”
mentioning
confidence: 99%